Statement of Number of Boys in Work Under the Conditions of our Agreement with the Home Office in October, 1937
1939 038-0084-001 STATEMENT OF NUMBER OF BOYS IN WORK UNDER THE CONDITIONS OF OUR AGREEMENT WITH THE HOME OFFICE IN OCTOBER, 1937. LONDON Offices 19 Bookshops 4 Hospital Laboratories 3 Restaurant 1 Cabinet Factory 1 Surgical Instruments Manufacturers 1 29 OUTSIDE LONDON Agricultural work 26 Garages 4 Electrical Engineers 4 Architect's Office 1 Boot-repairer 1 Engineering firm 1 Labortory 1 Cast Stone works 1 Joinery Works 1 Building Contractors 1 41 Total 70 292/946/38/84(I)